Vacancy trapping meachanism of multiple hydrogen/helium atoms in fcc-Fe: A first-principles study. Issue 1 (April 2020) - Zhao, Sen; He, Bin; Wang, Fei; Li, Rusong; Niu, Libo; Qu, Xin
Abstract: Using first-principles calculations, we studied the dissolution and diffusion behaviors of H/He atom in perfect fcc-Fe and vacancy capture multiple H/He atoms meachanism in fcc-Fe. The calculation results show that H/He atom prefers to occupy octahedral site, and they diffused along octahedral site-tetrahedral site-octahedral site in perfect fcc-Fe. Inside vacancy, H atom prefers to occupy octahedral site, while He atom prefers to occupy the vacancy center. The exist of H/He atom would decrease the vacancy formation energy. According to capture energies, a vacancy can trap five H atoms in fcc-Fe, but more He atoms can be accommodated even when the number of He atoms reaches sixteen. Therefore, the result provides an important theoretical basis to research the mechanism of hydrogen and helium embrittlement.